Enhancement of blast resistance of R.C beams using micro/nano silica in the presence of steel fibers - Mahmoud T. Nawar; Kareem A. El-Awady; Hamdy K. Shehab; Ahmed S. Eisa (Fracture and Structural Integrity)
The study investigates the effect of Micro/Nano silica and steel fibers on improving the dynamic response of R.C beams, using the ABAQUS/Explicit dynamic analysis. According to the results of Magnusson and Hallgren's experimental investigation, the FE model has been well-verified and calibrated. The FE test program has further been extended to study the effect of tensile reinforcement ratios ?? of 0.5%, 0.78%, and 1.13%, in comparison with the enhancement of concretes material properties, on the behavior of tested beams under blast loading. The results were compared in terms of changes in the max deflection at mid-span and flexural toughness values. The results showed that the flexural toughness of beams decreases when the tensile reinforcement ratio increases due to an increase in the moment of inertia (Ieffective).R.C beams incorporating SMCs (10%MS+1%NS) with different volume fractions (0%, 1%, 2%) of steel fibers showed that the concrete mixes with higher compressive strength values lead to an increase in the last beam deflection, producing a considerable rise in the flexural toughness by 18.2%, 27% and 31.8% for ?? (0.50%) and 15%, 19.9% and 23.6% for ?? (0.78%) and 6.6%, 13.7% and 19.6% for ?? (1.13%) respectively in comparison with the reference beam.